ESTIMATION OF HERITABILITY, CORRELATION AND PATH COEFFICIENT ANALYSIS IN FINE GRAIN RICE (Oryza sativa L.) - N. Akhtar; M. F. Nazir; A. Rabnawaz; T. Mahmood; M. E. Safdar; M. Asif; A. Rehman (Journal of Animal and Plant Sciences, 2011)
Yield contributing traits in ten rice genotypes were studied for variances, heritability, correlation (genotypic and phenotypic) and path coefficient analysis. The heritability was found to be highest for number of grains panicle-1, days to maturity, plant height and paddy yield while lowest for number of tillers plant-1. Paddy yield had strong genetic correlation with number of grains panicle-1, days to maturity and 1000-grain weight. Genotype PK4831-6-1 produced highest paddy yield (5.1 t ha-1), number of grains panicle-1 (144) as well as higher 1000-grain weight (25.56 g) whereas PK7909-27-1 and PK7378-4-1-1-1 achieved higher plant heights (162.5 cm and 148.6 cm, respectively) and spent longer growth duration (112 days) to reach maturity. Super Basmati produced highest number of tillers plant-1 (20) but lowest paddy yield (3.1 t ha-1). Regression analysis revealed that paddy yield had significant positive correlation with number of grains panicle-1 (b = 0.0164) and 1000-grain weight (b = 0.1356). It can be concluded that number of grains panicle-1, 1000-grain weight and days to maturity are important plant traits which should be considered when any breeding program for higher paddy yield in rice is to be planned.
Keywords: Correlation; fine rice; heritability; yield components